The Degree of Proficiency of Arabic Language Teachers in the Directorate of Special Education in the AL-quwaisma Brigade in the Competencies of E-Learning at a Distance from their Point of View - Abu Mohammed, Noor Mohammed Abdulaa (Dirasat: Educational Sciences, 2022)
Objectives: This study aimed at investigating the degree of Arabic language teachers possession of online learning form their point of views. Methods: This study used descriptive survey approach and the samples of the study were chosen randomly for the Arabic language teachers in the schools that follow private directorate of education at Al Qwismeh Directorate in Amman. 98 male and female Arabic teachers who were selected as a sample. Results: The study showed that the possession of Arabic teachers of online learning competencies were high; the competency of online evaluation is the on the first rank and the competency of dealing with the network and its program in the last rank . also , the results showed that there is no statistical differences (0.05) among the range of online education competencies . Conclusions: In light of the results, the study recommends the need to increase the awareness of teachers of the importance of using modern and effective means, and its role in improving and developing the outputs of distance education, and holding more courses and workshops specialized in the use of educational technology in the educational process, and focusing on the use of computers.